The meaning of the auxiliary morpheme 'dug in the aspect systems of some Central Tibetan dialects - Volkart, Marianne (2024)
The topic of this paper is a historical-comparative investigation of the meaning of the auxiliary morpheme 'dug in some Central Tibetan dialects. The interesting point about this morpheme is that it is used in apparently opposite meanings in the imperfective and perfective aspects. In the imperfective aspect, 'dug is used in many dialects for, roughly speaking, a "plus evidential" (+EVID) meaning, in order to express that the communicated information is based on the speaker's own experience or eyewitnessing. In the perfective aspect, on the other hand, 'dug appears in some dialects with a "minus evidential" (-EVID) meaning. In at least one case, namely Lhomi, these opposite meanings are even to be found within the same dialect.